Information needs and seeking behavior of patients and carers in palliative care: a case study from public hospital Malaysia - Mohamadali, Noor Azizah; Teoh Cy Oun, Cindy; Ahmad, Maznah; Mohammed, Siti Asma (2018)
Palliative care is associated with life-threatening diseases and death. To deepen understanding of the complexity of information need, information seeking behaviour becomes important in order to enhance the provision of adequate information and quality of services on the part of patients and carers in palliative care. This paper aims to investigate how patients and carer are seeking and use the information they need regarding palliative care. The study mainly assessed careers purpose of seeking information, preferable sources of health information and format, language and method of communication. The study used a quantitative method with the aid of structured questionnaires distributed among 45 respondents. The study found that the main purpose to seek information is to find out details of the illness they were diagnosed by the doctor (66%). Many also indicated searching for the possible location of care within their area of living as another purpose (59%). The preferences source of seeking information is by consulting with the doctors, followed by talking to family members, friends and consulting with allied health workers. In terms of seeking format of information related to their illness, most respondents preferred printed material (42%) as opposed to electronic (36%) or audiovisual materials (24%). They also mostly preferred information in the Malay language (85%) including of those Chinese respondents. The least preferred source of information is personal health blogs and apps. Respondents preferred a face-to-face meeting with the doctors (55%) as a method of communication. The paper then provides useful suggestions that would facilitate information seeking and use of the information they need among patients and careers in Malaysia and other countries with similar conditions.